PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR MENGHITUNG LUASTRAPESIUM DAN LAYANG-LAYANG DI KELAS V SD - Putri, Nindi Jolanda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of the this research was to know differences in learning outcomes of calculating broad trapezoid and kite using the cooperative model type Numbered Head Together (NHT) with convensional learning in class V SD 13 Parit Putus. This research design is quasi experiment with nonequivalent control group design. The sample in this study is class V SDN 13 Parit Putus,VA class is exsperiment class and VB class is control class. The results showed that there were influences in calculating flat bilding outcomes using the NHT type cooperative model with the convensional learning  in V SDN 13 Parit Putus,Agam. This is evidenced by the results of tcount 2.190 and t table at a significance level of 0.05 at 1.68595, so that t count> t table. Keyword : calculating broad trapezoid and kite, NHT